Utilization of Purple Sweet Potato Juice As an Alternative Violet Crystal in Coloring Streptococcus sp Bacteria and Escherichia coli - Ruhimat, Undang; Mutmainah, Rahayu Nirmatul; Ramdan, Siti Rahmah Kurnia; Firdaus, Nabil Ridla (JURNAL KESEHATAN STIKes MUHAMMADIYAH CIAMIS, 2024)
Gram staining is a staining method used to distinguish bacterial species into two major groups, namely Gram-positive and Gram-negative, Crystal violet is the primary (main) dye that will colour the target microorganisms. Staining in bacteria can be replaced using alternative substances with low cost, readily available and harmless, one of which uses substances that have anthocyanin content, namely purple sweet potato. The purpose of this study was to determine the results of using purple sweet potato as an alternative substance to replace crystal violet in staining Streptococcus sp and Escherichia coli bacteria. The method used is experimental. Based on the results of research that has been done on the use of purple sweet potato juice as an alternative substance to crystal violet in gram staining of Streptococcus sp and Escherichia coli bacteria, it shows that purple sweet potato material can be used at pH 6.5 and 5.7 while at pH 5.5 and 5 the bacteria are not perfectly coloured. So it can be concluded that purple sweet potato juice can be used as an alternative substance to Crystal violet in gram staining.